Gambaran Tingkat Stres Kerja Perawat Di Ruang IGD, ICU, Dan NICU RSUD Dr. H. Abdul Moeloek Bandar Lampung - Maulida, Syakira Zahra; Mayasari, Diana; Graharti, Risti; Sutarto, Sutarto (Medula, 2025)
Job stress is one of the factors that can lead to decreased performance. Occupations with the highest prevalence of work stress are owned by health workers. Nurses are more prone to stress than other health workers because nurses often have heavier workloads. The impact of stress that arises in the form of physiological, psychological and behavioral responses. the most influential factors causing nurses' work stress are individual and work factors. In addition, nurses in the emergency room and intensive care of hospitals are considered to have higher levels of job stress than other units. The purpose of this study was to determine the description of the level of work stress of emergency room, ICU, and NICU nurses at Dr. H. Abdul Moeloek Hospital Bandar Lampung. The type of research used is descriptive quantitative using primary data in the form of Perceived Stress Scale questionnaire. Sampling using proportional sampling technique with a total sample of 75 people consisting of 26 emergency room nurses, 26 ICU nurses, and 23 NICU nurses and the data will be analyzed univariately and then presented in tabular form. Based on the results of the study, 19 nurses (25.3%) were at a mild stress level and 56 nurses (74.7%) were at a moderate stress level. Levels of job stress that are too low or too high can lead to decreased job satisfaction and achievement so that it is necessary.